Sinus Floor Augmentation by Intraoral Endoscopic Approach for Biomaterial Study in a Rabbit Model - VALDIVIA-GANDUR, IVAN (In Vivo, 2019)
Aim: To develop a new surgical model for sinus floor augmentation (SFA) in rabbit for experimental purposes. Materials and Methods: Eight adult rabbits were used, two for a surgical design using the anatomical dissection study, and the other six for an endoscopically assisted intraoral approach of SFA unilaterally, creating a subantral space where an allograft biomaterial was deposited. SFA was verified through cone-beam computerized tomography. Healing, weight, food, feces, and behavior were evaluated for 4 weeks post-operatively. Results: All animals survived. There was no bleeding or infection; inflammation was mild. No changes were observed in terms of feeding, weight, feces, or behavior. Tissue healing was normal. Conclusion: This model is a refinement of the experimental technique and is a real option for SFA, without compromising animal morbidity because of its conservative design. The minimally invasive approach with endoscopic assistance reduces bias and improves surgical predictability.